You win in the locker room first : 7 C's to build a winning team in sports, business and life - Gordon, Jon, 1971- (Hoboken, N.J. : John Wiley & Sons, Inc., 2015)
Drawing on the extraordinary experiences of Coach Mike Smith and Jon Gordon consultant to numerous college and professional teams, this step-by-step book explores the seven powerful principles that any business, school, organization, or sports team can adopt to revitalize their organization. --
Description based on print version record and CIP data provided by publisher.
Keywords: Teams in the workplace; Leadership; Success; Electronic books